ANALISIS PENAMBAHAN LEM PUTIH POLY VINYL ACETATE TERHADAP SIFAT FISIK DAN MEKANIK BETON 1PC : 2 PS : 3 KR - Harprastanti, Primasiwi; Praharseno, Fikri; Supriyadi, Supriyadi; Sukoyo, Sukoyo; Wasino, Wasino (Politeknik Negeri Semarang, 2024)
The rapid development of concrete nowadays demands us to conduct research or further develop previous research. The goal is to produce higher quality concrete products. This research aims to determine the effect of adding Poly Vinyl Acetate white glue to the physical and mechanical properties of concrete with a ratio of 1PC: 2PS: 3KR. This research was conducted at the Materials Laboratory of the Civil Engineering Department, State Polytechnic of Semarang. The concrete produced in this study is in the form of cylinders with a diameter of 15cm, nine in total, and one beam measuring 15x15x60 cm. The samples produced consist of one sample of normal concrete and four samples with PVAc glue mixtures (2.5%, 5%, 7.5%, and 10%). The research results show that the addition of glue has little effect physically. The percentage results of compressive strength of cylinders at 7 days of age with normal concrete are as follows: PVAc 2.5% increased by 12.96%; PVAc 5% increased by 4.78%; PVAc 7.5% decreased by 14.68%; PVAc 10% decreased by 39.57%. At 14 days of age, with normal concrete: PVAc 2.5% increased by 16.66%; PVAc 5% decreased by 3.65%; PVAc 7.5% decreased by 20.93%; PVAc 10% decreased by 52.10%. At 28 days of age, with normal concrete: PVAc 2.5% decreased by 6.13%; PVAc 5% decreased by 13.24%; PVAc 7.5% decreased by 20.69%; PVAc 10% decreased by 48.86%. As for the flexural strength results of beams at 28 days of age, concrete with PVAc content: 2.5% decreased by 32.09%; 5% decreased by 45.56%; 7.5% decreased by 36.51%; 10% decreased by 33.88%. These results are compared with normal concrete.